2009
DOI: 10.1136/oem.2008.045500
|View full text |Cite
|
Sign up to set email alerts
|

Cross-validation and refinement of the Stoffenmanager as a first tier exposure assessment tool for REACH

Abstract: Objectives For regulatory risk assessment under REACH a tiered approach is proposed in which the first tier models should provide a conservative exposure estimate that can discriminate between scenarios which are of concern and those which are not. The Stoffenmanager is mentioned as a first tier approach in the REACH guidance. In an attempt to investigate the validity of the Stoffenmanager algorithms, a cross-validation study was performed.Methods Exposure estimates using the Stoffenmanager algorithms were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 38 publications
2
72
0
Order By: Relevance
“…A worst case estimation based on the 90th percentile of the exposure distribution or other percentile of the exposure distribution can be assessed. [21,24] Based on the observations, the maximum concentration of sevoflurane in a mixture of breathing gases was assumed to be 3%, as the worst possible scenario. Air samples were collected for at least 6 h, but the employees were not exposed to anaesthetics throughout the whole work shift.…”
Section: Methodsmentioning
confidence: 99%
“…A worst case estimation based on the 90th percentile of the exposure distribution or other percentile of the exposure distribution can be assessed. [21,24] Based on the observations, the maximum concentration of sevoflurane in a mixture of breathing gases was assumed to be 3%, as the worst possible scenario. Air samples were collected for at least 6 h, but the employees were not exposed to anaesthetics throughout the whole work shift.…”
Section: Methodsmentioning
confidence: 99%
“…(3) The regression models have recently been further tested and refined in a cross-validation study. (4) Stoffenmanager is proposed as one of the available generic Tier 1 tools for exposure assessment under REACH, the European chemicals legislation. Manufacturers and importers of dangerous substances are required to develop exposure scenarios that describe how risks of the substances can be controlled for workers, the general population, and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Validation studies of the quantitative exposure part of Stoffenmanager (Koppisch et al 2012;Schinkel et al 2010) showed that it was sufficiently conservative; however, no study has evaluated the reliability of either the quantitative exposure part or the control banding part to explore whether and how the results vary when multiple users study the same scenarios.…”
Section: Modern Control Banding Strategies Were Developed In the Coshmentioning
confidence: 99%
“…= with protection. Working in a cabin 3 0.03-1 (a) a: (Marquart et al 2008) b: (Schinkel et al 2010) c : 8 is for liquids and 14 is for dusts 2 This scenario is outside the scope of Stoffenmanager and will therefore only be presented in tables.…”
Section: Acknowledgementmentioning
confidence: 99%
See 1 more Smart Citation